ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DOMESTIK REGIONAL BRUTO (PDRB) DI SUMATERA UTARA DENGAN PENDEKATAN REGRESI DATA PANEL - Rosni, Rosni; Rivai, Muklas; Nainggolan, Lorena Ulitara (LPPM Universitas Bina Bangsa, 2025)
Gross Regional Domestic Product (GRDP) is an indicator in measuring the economic growth of a region. In this research, the aim is to analyze the factors that influence GRDP in North Sumatra in 2012-2023 using the panel data regression method. Panel data regression analysis is a statistical method that combines time series and cross-section data to capture dynamics over time and differences between regions more comprehensively. The independent variables analyzed include Per Capita Expenditure, Original Regional Income (PAD), Population Density, Education Level, and Poverty Level. The selection of the best regression model was carried out through the Chow Test and Hausman Test, which showed that the Fixed Effect Model (FEM) was the most appropriate model. And it was found that the variables PAD, Education Level, and Poverty Level had a significant influence on GRDP, while Per Capita Expenditure and Population Density did not have a partially significant influence.